METHODS FOR EARLY DETECTION OF CLINICAL SIGNS OF ORAL MUCOSAL CANCER - Baxodurov Botirxon Nodir oʻgʻli (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: Oral mucosal cancer, particularly oral squamous cell carcinoma (OSCC), remains one of the most prevalent and aggressive malignancies in the head and neck region. Early diagnosis significantly improves prognosis and treatment outcomes; however, early clinical signs are often subtle and easily overlooked. This article reviews the current methods used for the early detection of oral cancer, including visual-tactile examination, toluidine blue staining, autofluorescence imaging, brush biopsy, and emerging adjunctive diagnostic technologies. Emphasis is placed on the importance of routine oral cancer screening by dental professionals and the identification of high-risk lesions such as leukoplakia, erythroplakia, and non-healing ulcers.